TAHLÎL AL-HÂJÂT AL-KHÂSHSHAH LI MUTA'ALLIMÎ AL-LUGHAH AL-'ARABIYAH LI AGHRÂDH KHÂSHSHAH - Eltingari, Salih Mahgoub; binti Abdullah, Nurul Shifaah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
The paper presents an analysis on the specific needs of the Arabic Language for students of Islamic Studies at the Faculty of Islamic Reveal Knowledge and human Sciences. The study was carried out using descriptive analysis method to answer the research question: What are the needs of Islamic studies’ students from the Arabic language? A questionnaire as a research tool was distributed to 88 respondents and the data collected were analyzed using Statistical Package for the Social Sciences (SPSS) software. The results showed that the respondents’ needs from four language skills for academic purposes with the following rankings: Listening - Reading - Writing – Speaking. Conversely, for the career purposes with these following rankings: Reading – Writing – Speaking. The research recommends the importantance of determining the Arabic Language for specific purposes based on the students’ needs, and thus, designing the courses based on the analysis gathered.